Small Watershed Runoff Generation Model - Sarangi, A.; Bhattacharya, A.K.; Mishra, K. (Journal of Soil and Water Conservation, 2022)
A small Watershed Runoff Generation Model (SWARGEM) was developed for a square grid-wise discretised watershed to consider the spatial variation of the morphological, soil and landuse features. Grid-wise water budgeting was done and the excess was routed to the outlet. This procedure was followed for the entire watershed and up to the desired duration of the Direct Runoff Hydrograph. Manning's equation was used for flow routing. The model was developed for the Banha watershed, near the Hazaribagh town in Bihar, in the Upper Damodar Valley and was validated for 35 storm events. Wilcoxon matched-pair signed-rank test revealed no significant difference between the model-predicted and the observed runoff at 0.05 size of type I error.